Catching aggression from one's peers: A longitudinal and multilevel analysis. Issue 2 (4th February 2019) - Jung, Janis; Busching, Robert; Krahé, Barbara
Abstract: Exposure to peer aggression is a major risk factor for the development of aggressive behavior in childhood and adolescence. Furthermore, peer aggression has the propensity to spread and affect individuals who were not exposed to the original source of aggression. The aim of this paper is to demonstrate that peer aggression is in many regards similar to a contagious disease. By presenting a program of research based on longitudinal and multilevel studies, we provide evidence for the contagious quality of aggressive behavior, show that individuals vary in their susceptibility to peer aggression, and describe group‐level characteristics that moderate the influence of peer aggression. We discuss mechanisms that may explain how individuals catch aggressive behavior from their peers and how the effects on the development of individuals' aggressive behavior unfold over time. Further, we examine processes that may increase the risk of being exposed to peers' aggressive behavior. We conclude with discussing implications for future studies on the contagious nature of peer aggression.